Insights into the Multi-Azole Resistance Profile in Candida haemulonii Species Complex - Laura Nunes Silva; Lívia de Souza Ramos; Simone Santiago Carvalho Oliveira; Lucas Barros Magalhães; Eamim Daidrê Squizani; Lívia Kmetzsch; Marilene Henning Vainstein; Marta Helena Branquinha; André Luis Souza dos Santos (Journal of Fungi, 2020)
The Candida haemulonii complex (C. duobushaemulonii, C. haemulonii, and C. haemulonii var. vulnera) is composed of emerging, opportunistic human fungal pathogens able to cause invasive infections with high rates of clinical treatment failure. This fungal complex typically demonstrates resistance to first-line antifungals, including fluconazole. In the present work, we have investigated the azole resistance mechanisms expressed in Brazilian clinical isolates forming the C. haemulonii complex. Initially, 12 isolates were subjected to an antifungal susceptibility test, and azole cross-resistance was detected in almost all isolates (91.7%). In order to understand the azole resistance mechanistic basis, the efflux pump activity was assessed by rhodamine-6G. The C. haemulonii complex exhibited a significantly higher rhodamine-6G efflux than the other non-albicans Candida species tested (C. tropicalis, C. krusei, and C. lusitaneae). Notably, the efflux pump inhibitors (Phe-Arg and FK506) reversed the fluconazole and voricolazole resistance phenotypes in the C. haemulonii species complex. Expression analysis indicated that the efflux pump (ChCDR1, ChCDR2, and ChMDR1) and ERG11 genes were not modulated by either fluconazole or voriconazole treatments. Further, ERG11 gene sequencing revealed several mutations, some of which culminated in amino acid polymorphisms, as previously reported in azole-resistant Candida spp. Collectively, these data point out the relevance of drug efflux pumps in mediating azole resistance in the C. haemulonii complex, and mutations in ERG11p may contribute to this resistance profile.